Emotional Dynamics, Dialogue, And Organizational Innovativeness Of Indonesian Private Tv Stations - Dodie Tricahyono (Jurnal Manajemen Indonesia, 2021)
Currently, researchers tend to suggest a socially based approach to address the challenge of innovation rather than an economic approach which often fails to address the challenge. This study examines the relationship between emotional dynamics as an independent variable, organizational innovativeness as the dependent variable, and dialogue as a mediator in Indonesian private television broadcasting institutions. Data is collected from 132 respondents who are creative workers at Indonesian private tv stations. Prior to hypotheses testing, this study conducted a factor analysis to check the construct validity of all variables under study. This study used multiple regression analysis to examine direct relationships and two-step hierarchical regression to examine mediating effect. The results show that emotional dynamics have a significant effect on organizational innovativeness and dialogue. The results also show that dialogue partially mediates the relationship between emotional dynamics and organizational innovativeness. This study found that organizational innovativeness can be achieved by those who apply: an open culture, a climate of discussion about new ideas, and a climate of mutual respect. The study also reveals that dialogue is a very important tool that mediates the relationship between open culture and organizational innovativeness. This study proposes that organizational age and the influence of national culture need to be considered for further research on social-based innovation.